Methotrexate efficacy, but not its intolerance, is associated with the dose and route of administration - Fráňová, J. (Pediatr Rheumatol Online J, 2016)
BACKGROUND: There is a lack of published evidence on the importance of methotrexate (MTX) dose and route of administration on both its efficacy and adverse events in children with Juvenile Idiopathic Arthritis (JIA). We aimed to document our clinical practice based on the treat-to-target approach in order to support the concept that better therapeutic effect achieved with an optimal dose of parenteral MTX is associated with clinically acceptable adverse effects comparable to those reported for oral treatment. METHODS: Study inclusion criteria were indication of new MTX therapy for active arthritis in confirmed JIA patients younger than 18 years. Eligible patients were evaluated prospectively every 3 months for 1 year using standardized instruments for treatment response (American College of Rheumatology Pediatric (ACRPedi) response, Juvenile Arthritis Disease Activity Score (JADAS) 71, Clinically Inactive Disease (CID)) and adverse events (laboratory monitoring, Methotrexate Intolerance Severity Score (MISS)). MTX responders had to achieve at least ACRPedi 70 response. MTX intolerance was defined by MISS ≥ 6. RESULTS: In 45/55 patients (81.8 %) MTX was started as subcutaneous injection. The initial median weekly dose was 14.4 mg/m(2) in parenteral and 11.7 mg/m(2) in oral administration. MTX therapy was effective in the level of ACRpedi70 and CID in 50.9 % and 30.9 % of patients at month 6 and in 70.9 % and 56.4 % after 12 months of the treatment, respectively. MTX intolerance at 6 and 12 months was noted in 25.5 % and 30.6 %, respectively. Management of intolerance included change in the dose and/or route of administration, education and councelling. Adverse events led to MTX withdrawal in 5 patients (9 %) due to toxicity (n = 3) and intolerance (n = 2). We did not find any significant predictive factors for either MTX therapeutic response or intolerance. CONCLUSION: Subcutaneous MTX weekly dose around 15 mg/m(2) is associated not only with a high response rate within the first 12 months of treatment, but also with a relatively low rate of significant adverse effects that would lead to the treatment termination. It allows early recognition of MTX non-responders and addition of biologic therapy. Sustainability of therapeutic effect and longer-term evolution of adverse events will be addressed by an ongoing extension of the study.